Implementation of industry-oriented animal welfare and quality assurance assessment tools in commercial cattle feeding operations - Barnhardt, Tera Rooney (Kansas State University, 2015)
Consumer interest in production agriculture has prompted the beef industry to develop tools to increase accountability of producers for animal management practices. The Beef Quality Assurance Feedyard Assessment, developed by veterinarians, animal scientists, and production specialists, was used to objectively evaluate key areas of beef cattle production such as animal handling, antimicrobial residue avoidance, and cattle comfort in 56 Kansas feedyards. During the assessment, management protocols were reviewed, facilities and pens were inspected, and cattle handling practices were observed. Of the 56 feedyards, 19 maintained complete and current Best Management Practices documentation for all management protocols required by the assessment. During assessment of cattle handling practices, 78.6% of feedyards met requirements for an Acceptable score for all measured criteria. An electric prod was used on only 4.0% of cattle during processing. In addition, 83.0% of feedyards scored Acceptable for stocking rate, feed bunk, water tank, and mud score standards.
Keywords: BQA assessment tools; Audit; Cattle; Feedyard; Quality assurance; Welfare; Animal Sciences (0475)